Wissenschaftliche Konferenzen in Social Virtual Reality - Raphael Zender; Miriam Mulders (FernUniversität Hagen, 2022)
In November/December 2020, one of the first scientific conferences per Social Virtual Reality (SocialVR) was held. The conference, which lasted several weeks, addressed the anchoring of virtual and augmented reality (VR/AR) technologies in vocational education. The focus was also on examining the suitability of the immersive medium as an educational technology for the conference setting. This paper describes the conception and implementation of the conference with regard to the special characteristics of SocialVR. Furthermore, the results of the evaluation are presented, which explores the question of what strengths and weaknesses SocialVR has in store for online academic conferences.